Community-Led Waste Management and Wastewater Treatment Initiatives in Kalicode: A Holistic Approach to Public and Environmental Health - Hannun, Syaharanie Mulya (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
This study explores the community-driven waste bank and IPAL (Portable Wastewater Treatment Plant) initiatives in Kalicode, underscoring their pivotal role in promoting public health and environmental well-being. Originating from landfill overflow, the waste bank addresses improper waste disposal and river pollution, showcasing tangible benefits such as reduced garbage accumulation and minimised vector-borne diseases. Simultaneously, the IPAL responds to poor sanitation and wastewater discharge, significantly contributing to public health by preventing pollution and enhancing air quality. Despite their successes, limited government involvement poses challenges, emphasising the need for increased support to fully realise the potential impact on public and environmental health.